Predictors of Chronic Postsurgical Pain in Elderly Patients Undergoing Hip Arthroplasty: A Multi-Center Retrospective Cohort Study - Lu Y; Hu B; Dai H; Wang B; Yao J; Yao X (International Journal of General Medicine, 2021)
Yi Lu,1,* Bang Hu,2,* Haitao Dai,3,* Bao Wang,1 Jiayin Yao,4 Xinhua Yao1 1Department of Anesthesiology, The Affiliated TCM Hospital of Guangzhou Medical University, Guangzhou, Guangdong Province, People’s Republic of China; 2Department of Colorectal Surgery, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, The Sixth Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong Province, People’s Republic of China; 3Department of Interventional Radiology, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong Province, People’s Republic of China; 4Department of Gastroenterology, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, The Sixth Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinhua YaoDepartment of Anesthesiology, The Affiliated TCM Hospital of Guangzhou Medical University, 16th Zhuji Road, Guangzhou, Guangdong Province, 510130, People’s Republic of ChinaTel +86 13719289709Email yxh200210@126.comJiayin YaoDepartment of Gastroenterology, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, The Sixth Affiliated Hospital of Sun Yat-Sen University, 26th Yuancun Second Road, Guangzhou, Guangdong Province, 510655, People’s Republic of ChinaTel +86 13826462890Email yjyin@mail3.sysu.edu.cnBackground: Identifying patients at high risk of developing chronic postsurgical pain (CPSP) is of extreme importance in order to help launch appropriate therapeutic strategies and intensive initiation of pain management.Aim: In this study, we aimed to conduct a multi-center retrospective cohort study to establish a prognostic model and a nomogram to predict the risks of CPSP in elderly patients who underwent hip arthroplasty at 6 months postoperatively.Methods: We collected data from 736 patients aged > 65 years who had undergone hip arthroplasty from October 1, 2016 to September, 30, 2018 at multiple tertiary referral centers in Guangzhou, China. All data were randomly stratified into a training set and a testing set at a ratio of 8:2. Data were analyzed via multiple logistic regression analysis with receiver operating characteristic (ROC) curves and areas under the curve. This model was further validated by estimating calibration and discrimination. A nomogram was ultimately developed.Results: A total of 736 eligible patients were enrolled, 27.20% of whom developed CPSP within 6 months postoperatively. Preoperative pain in the surgical area (OR=2.456, 95% CI:1.814– 3.327, P< 0.001), preoperative depression state (OR=1.256, 95% CI:1.146– 1.378, P< 0.001), surgical type (OR=7.138, 95% CI:3.548– 14.364, P< 0.001), acute postoperative numerical rating scale score (OR=5.537, 95% CI:3.607– 8.499, P< 0.001) and analgesic type (patient-controlled epidural analgesia: OR=0.129, 95% CI:0.055– 0.299, P< 0.001; patient-controlled intravenous analgesia: OR=0.033, 95% CI:0.011– 0.097, P< 0.001) were identified as independent significant factors associated with CPSP. A prognostic model was established and further validated. An ROC curve confirmed the predictive ability of this model with a high sensitivity value of 92.12% (95% CI:86.90– 95.74) and specificity value of 91.72% (95% CI:88.77– 94.11). A nomogram was developed to simplify the use of the predictive model in clinical practice.Conclusion: This prognostic model could be of great value in clinical practice, serving as the basis for early personalized analgesic management of elderly patients undergoing hip arthroplasty.Keywords: chronic postsurgical pain, CPSP, prognostic model, nomogram, retrospective study